Case Report: Jet lag and travel fatigue effects on performance in a world-class paralympic shot-putter after eastward long-haul transmeridian travel - Farias-Valenzuela, C (Frontiers Media SA, 2026)
Introduction: This case report aimed to examine the effects of long-haul eastward transmeridian travel on neuromuscular performance, subjective well-being, and internal training load in a World-class female Paralympic shot-putter preparing for the Paris 2024 Paralympic Games. Methods: An F54-class athlete was monitored for 21 days surrounding a flight from Chile to France (eastward, six time zones). Daily assessments included handgrip strength (HGS), shot-put throwing distance, subjective well-being, and session rating of perceived exertion (s-RPE). Descriptive statistics and Spearman s correlation were used to explore relationships between performance and physiological/subjective variables. Results: Transient reductions in HGS occurred for 3–4 days post-travel, followed by daily fluctuations. Jet lag and fatigue scores were elevated during the first post-travel days but showed progressive improvement, returning to near-baseline levels by approximately two weeks before competition. Throwing performance showed a moderate positive correlation with left-hand HGS (ρ = 0.52, p = 0.032) and a negative correlation with s-RPE (ρ = –0.56, p = 0.018). Gastrointestinal disruptions, particularly in stool frequency and consistency, persisted longer than other subjective variables. Conclusion: Long-haul transmeridian travel was associated with transient neuromuscular and perceptual disturbances in a world-class Paralympic athlete. HGS and s-RPE emerged as practical and responsive markers of travel-induced fatigue and performance readiness during the 21-day period surrounding international travel. These findings highlight the need for individualized monitoring strategies during the travel adaptation period in elite Paralympic sport contexts. 2026 Garcia-Carrillo, Thapa, Hermosilla-Palma, Alarcón-Rivera, Farías-Valenzuela, Azócar-Gallardo, Yáñez-Sepúlveda, Olivares-Arancibia, Castillo-Paredes, Calleja-González, Judge, Fuentes-Barría and Mello.